From Ikaria to the stars : classical mythification, ancient and modern - Green, Peter, 1924- (University of Texas Press, 2004)
Annotation "I hadn't, till I really started digging, gauged the fierce intensity of the need for myth in the human psyche, of any age, or sensed the variety of motives dictating that need," writes Peter Green in the introduction to this wide-ranging collection of essays on classical mythology and the mythic experience. Using the need for myth as the starting point for exploring a number of topics in Greek mythology and history, Green advances new ideas about why the human urge to make myths persists across the millennia and why the borderland between mythology and history can sometimes be hard to map. Green looks at both specific problems in classical mythology and larger theoretical issues. His explorations underscore how mythic expression opens a door into non-rational and quasi-rational modes of thought in which it becomes possible to rewrite painful truths and unacceptable history--which is, Green argues, a dangerous enterprise. His study of the intersections between classical mythology and Greek history ultimately drives home a larger point, "the degree of mythification and deception (of oneself no less than of others) of which the human mind is capable."